2021
DOI: 10.1038/s41467-021-25395-9
|View full text |Cite
|
Sign up to set email alerts
|

Vacancy control in acene blends links exothermic singlet fission to coherence

Abstract: The fission of singlet excitons into triplet pairs in organic materials holds great technological promise, but the rational application of this phenomenon is hampered by a lack of understanding of its complex photophysics. Here, we use the controlled introduction of vacancies by means of spacer molecules in tetracene and pentacene thin films as a tuning parameter complementing experimental observables to identify the operating principles of different singlet fission pathways. Time-resolved spectroscopic measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 57 publications
3
20
1
Order By: Relevance
“…13,20,30 Importantly, we can not only conclude that SF is the main decay path of the free exciton, but our results for ADT blends also allow us to elucidate its microscopic mechanism. The linear dependence of the SF rate on the chromophore concentration has been observed before for TET and referred to as the replacement effect, 52,53 indicating that SF occurs via incoherent population transfer from S 1 to 1 (TT). The deviation from this linear dependence found for TET blends with low ADT fractions can be explained by the similar band gaps of ADT and TET, which makes an excitation of solely ADT impossible and can also enable an energy transfer from ADT to TET.…”
Section: ■ Results and Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…13,20,30 Importantly, we can not only conclude that SF is the main decay path of the free exciton, but our results for ADT blends also allow us to elucidate its microscopic mechanism. The linear dependence of the SF rate on the chromophore concentration has been observed before for TET and referred to as the replacement effect, 52,53 indicating that SF occurs via incoherent population transfer from S 1 to 1 (TT). The deviation from this linear dependence found for TET blends with low ADT fractions can be explained by the similar band gaps of ADT and TET, which makes an excitation of solely ADT impossible and can also enable an energy transfer from ADT to TET.…”
Section: ■ Results and Discussionmentioning
confidence: 59%
“…50 However, the admixture of these states can be considered small for several reasons. From a theoretical standpoint, calculations on pentacene 37,55 and tetracene 56 only showed a small admixture of these states to the 1 (TT) state and since SF is occurring via the coherent mechanism in pentacene, 52 while, in contrast, we showed that in ADT the incoherent SF mechanism is driving SF, it can be expected that the admixture of these states is even smaller in ADT than in pentacene. 57 Additionally, from an experimental viewpoint, a large admixture of such states to 1 (TT) would make the 1 (TT) state visible in absorption and photoluminescence spectroscopy without the need for Herzberg−Teller coupling, 55 which, however, contrasts with our results.…”
Section: ■ Results and Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Compared to the Frenkel exctions, CT excitons usually possess only small oscillatory strength making these hard to excite and observe experimentally. 3 The CT-like excitonic contributions are considered as an important ingredient in photovoltaic applications and fast singlet exciton fission rates in molecular solids, 28–30 which has a potential to improve the power conversion efficiency of solar cells. Therefore, identifying the CT-like nature of the excitations at the absorption edge is crucial.…”
Section: Introductionmentioning
confidence: 99%